ULTRAVIOLET RADIATION INDUCED CHANGES IN THE PRODUCTION OF ORGANIC COMPOUNDS IN ANTARCTIC MARINE PHYTOPLANKTON (18th Symposium on Polar Biology) - / ハンダ, ノブヒコ; スズキ, コウジ; タグチ, サトル; ハマ, タケオ; GOES, Joaquim I.; HANDA, Nobuhiko; SUZUKI, Koji; TAGUCHI, Satoru; HAMA, Takeo (National Institute of Polar Research, 1997)
P(論文) Experiments were conducted during January 1995 in the Southern Ocean to examine the impact of enhanced solar ultraviolet-B radiation (UVBR) on the biosynthesis and composition of organic compounds in Antarctic marine phytoplankton. Our results revealed distinct changes in the biochemical composition of phytoplankton attributable to UVBR exposure. Fatty acid concentrations increased in the presence of UVBR, mainly on account of a large increase in the content of saturated fatty acids within the cells. On the other hand, polyunsaturated fatty acids declined in cells exposed to UVBR. Amino acid concentrations were higher in the UVBR exposed samples, attributable largely to a UVBR induced increase in cellular concentrations of glutamic' acid (glutamic acid+glutamine) and aspartic acid. Monosaccharide constituents of cellular storage and structural carbohydrates, however, showed a decline in the cells exposed to UVBR. Except for the decline in structural monosaccharides, these changes in the patterns of organic compounds observed in Antarctic phytoplankton were remarkably similar but, greater in magnitude in comparison to those observed in temperate phytoplankton exposed to UVBR. departmental bulletin paper